A novel supraorbital surgical approach for enucleation in dromedary camels (Camelus dromedaries): cadaveric study - Marzok, Mohamed; Nazih, Mohamed A; Almubarak, Adel I; El-Sherif, Mohamed W (BMC veterinary research, 2024)
Enucleation and exenteration are widely utilized ophthalmic procedures in veterinary practice, involving the complete removal of the eye and comprehensive extraction of orbital contents, respectively. These procedures are indicated for pain relief, excision, and management of neoplasia metastases, and addressing severe medically untreatable conditions. This study aimed to develop an orbital enucleation surgical approach. The study evaluated the applicability of the new approach and investigated the impact of the surgical procedure. Anatomical dissection of three cadaveric heads and surgical orbital enucleation in four cadaveric heads were performed. Anatomical data was collected, and feasibility, safety and applicability of the procedure were assessed. Anatomical dissection showed a distinctive large orbital fossa, providing a suitable surgical window to access orbital structures. The procedure was found to be feasible, facilitating the complete removal of the orbital content. Notably, the preservation of intact eyelids was prioritized to enhance cosmetic appearance. The presented orbital enucleation technique proved to be feasible, safe, reproducible, and required basic surgical skills to perform.